2022
DOI: 10.7759/cureus.31715
|View full text |Cite
|
Sign up to set email alerts
|

Topography of the Anatomical Landmarks of Carotid Bifurcation and Clinical Significance

Abstract: Objective: Carotid bifurcation (CB) and its terminal branches are the most common sites of atherosclerotic plaques. In surgical treatment, these plaques can be reached by an endarterectomy technique. The success of the technique can be achieved with good anatomical knowledge of these arteries and their relationships with surrounding structures.Materials and methods: The study was performed retrospectively on archived images of patients with computed tomography angiography (CTA). Two hundred forty-seven patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 31 publications
0
0
0
Order By: Relevance
“…Different vertical locations of the CB were found in the present study and others [ 1 , 3 5 , 9 , 11 , 12 , 14 , 17 , 19 , 21 , 24 , 25 , 27 37 ]. As presented in Table 7 , different studies observed only the vertebral level of the CB; other authors studied the CB in relation to different anterior cervical landmarks, while a few authors observed both vertebral and anterior cervical landmarks.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…Different vertical locations of the CB were found in the present study and others [ 1 , 3 5 , 9 , 11 , 12 , 14 , 17 , 19 , 21 , 24 , 25 , 27 37 ]. As presented in Table 7 , different studies observed only the vertebral level of the CB; other authors studied the CB in relation to different anterior cervical landmarks, while a few authors observed both vertebral and anterior cervical landmarks.…”
Section: Discussionsupporting
confidence: 56%
“…Our results converge with the conclusions of a previous study of the anterior and posterior landmarks of the CB. Cihan and Deveci (2022) concluded that estimating the CB’s location according to the gonion and hyoid bone will give a more accurate result [ 11 ]. Cobiella et al (2021) used the body of the hyoid bone level as a single landmark for the CB [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the anatomy of the CB is highly variable concerning its vertical position [11][12][13][14][15], its relationship with the hyoid bone [16], and its axial spin. In previous studies, the vertical position of the CB was referred to vertebral landmarks, anterior cervical landmarks, or both [17][18][19][20][21][22][23][24][25][26]. The twisted carotid artery (TCA)-or ECA and ICA transposition, or twisted CB-is a variant in which the ICA is medial to the ECA [27,28].…”
Section: Discussionmentioning
confidence: 99%